2002
DOI: 10.1016/s0167-4889(01)00187-2
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol (−)-epigallocatechin 3-gallate inhibits MMP-2 secretion and MT1-MMP-driven migration in glioblastoma cells

Abstract: We have recently shown that green tea polyphenols, and especially (-)-epigallocatechin 3-gallate (EGCg), acted as potent inhibitors of matrix metalloproteinase activities as well as of proMMP-2 activation (M. Demeule, M. Brossard, M. Page, D. Gingras, R. Beliveau, Biochim. Biophys. Acta 1478 (2000)). In the present work, we sought to examine the involvement of MT1-MMP in the EGCg-induced inhibition of proMMP-2 activation. The incubation of U-87 glioblastoma cells in the presence of concanavalin A or cytochalas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 46 publications
4
96
0
1
Order By: Relevance
“…28 Inhibition of MMPs has also been reported in several studies of phenolics compounds from green tea. [29][30][31] The reduction in total cell number in the Matrigel invasion assay was not due to cytotoxicity, as demonstrated in cell viability study (data not shown). In the assay of cell attachment to plastic substrate, there were no significant effects of either OVP or the isolated phenolics (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…28 Inhibition of MMPs has also been reported in several studies of phenolics compounds from green tea. [29][30][31] The reduction in total cell number in the Matrigel invasion assay was not due to cytotoxicity, as demonstrated in cell viability study (data not shown). In the assay of cell attachment to plastic substrate, there were no significant effects of either OVP or the isolated phenolics (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…One common intracellular pathway may also involve Ca 2ϩ /calmodulin-dependent signaling, which has been shown to regulate MT1-MMP cell surface processing (25), as well as the phosphorylation of CD44 required for cell migration on HA (62). Finally, we also report that EGCg, an effective inhibitor of MT1-MMP-mediated functions (36,63), also antagonized MT1-MMP-mediated cell surface HA-binding.…”
Section: Discussionmentioning
confidence: 51%
“…C, carbonate extraction was performed as described under "Experimental Procedures"; lysates were fractionated in a discontinuous sucrose density gradient. anti-angiogenic and anti-MMP inhibitory activities (35)(36)(37). We demonstrated that HA cell surface binding in control glioma cells treated for 1 h with either ilomastat or EGCg had no effect (Fig.…”
Section: Cholesterol Depletion Increases the Cell Surface Binding Of mentioning
confidence: 90%
“…(Ϫ)Epigallocatechin-3-gallate (EGCG) is the major bioactive polyphenol present in green tea. It possesses anti-oxidant (16), anti-mutagenic (17), anti-proteolytic (18,19), and anti-proliferative activity (20). In addition, it has been shown to increase p27 KIP-1 levels, inhibit cyclin activity, and inhibit cell cycle progression (21,22).…”
mentioning
confidence: 99%